Social auditing in the organizations of the cooperative sector: precedent of remarkable governance scenario - Rubio-Rodriguez, Gustavo Adolfo; de Almeida Santos, Fernando (REVESCO. Revista de Estudios Cooperativos, 2021)
Cooperative organizations form an increasingly visible and relevant sector, whose purpose strengthens the policy of providing a response to specific welfare needs of individuals, communities and society in general. The purpose of this paper is to highlight the importance of social auditing in cooperative sector organizations, as a response derived from diligent governance practices; to this end, seven specialized saving and credit cooperatives defined by Colombian legislation as an autonomous association of persons who have voluntarily joined together to address their economic, social and cultural insufficiencies and aspirations were taken. The findings show that auditing when fully administered, forges the fulfilment of strategic social objectives, i.e. to use the resources of the specific earmarked funds in their own activities, such as formal education, health, funeral aid and other partner welfare activities; duly approved by the competent body, disclosed in its management reports and financial information. As a conclusion, the governance of the cooperatives studied underpins their scaffolding on the success of the choice of the members of the audit committees, who exercise effective control over the resources with specific allocation.
Keywords: Social economy; Governance model; Cooperative organization; Social responsibility; Solidary sector